The Influence of Environmental Performance Towards Creating Shared Value on Sri-Kehati Index - Wibowo, Aulya Yulianti; Rahardja, Liana (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This research explores the influence of environmental performance on the concept of Creating Shared Value (CSV). CSV is a business approach that simultaneously promotes value creation for companies and society. About environmental performance, this study analyzes how environmentally friendly business practices can become a fundamental pillar of CSV strategy. We examine the relationship between corporate actions in reducing negative environmental impacts and increasing shared values through social welfare and business sustainability. By engaging case studies from various industries, we illustrate how proactive measures on environmental issues can generate long-term mutually beneficial benefits focused on creating shared value. UU No. 40 Tahun 2007 reads, "A company's social and environmental responsibility is its commitment to engage in sustainable economic development to enhance the environment and quality of life for the company, the local community, and society at large". Social and environmental responsibility is the company's commitment to sustainable economic development. This aims to enhance the standard of living and the environment to benefit the company, the local community, and society. The method used is multiple linear regression. Environmental performance indicators influence the company size, type of industry and capital intensity, significantly affecting CSV. The theoretical contribution of this research is to provide research results on the influence of environmental performance on CSV quantitatively and empirically in Indonesia because this topic is rarely discussed using a quantitative and empirical approach. The practical contribution expected from this research is that it can provide additional information to analyze company performance comprehensively by considering financial and environmental performance. Meanwhile, contributions from regulators related to the accounting sector, such as the Indonesian Accountants Association, could consider requiring sustainability reports for companies traded on the Indonesian Stock Exchange so that companies can be sustainable.